DEVELOPMENT OF APPLICATION MALABARU AS LEARNING MEDIA SPACE BUILDING MATERIAL IN GRADE V ELEMENTARY SCHOOL - Marwan Maulana; Maulana; Isrok'atun (Universitas Majalengka, 2025)
This study aims to identify the extent to which the results of the development of the MALABARU (Mari Belajar Bangun Ruang) application as a learning media for spatial geometry material in grade V of Elementary School. This application contains material on the types and properties of spatial geometry, spatial geometry nets, and how to calculate the surface area and volume of spatial geometry. This application is packaged in several features such as explanatory materials, learning videos, and educational games. The research method used in this study is Research and Development (RnD) using the ADDIE model which includes five stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were 39 grade V Elementary School students. The results of this study are that the learning media developed has been validated by three media experts with an average score of 95%, two material experts with an average score of 100%, and three language experts with an average score of 97.3% which indicates that the MALABARU application learning media is very suitable for use in the learning process. The results of the student questionnaire obtained an average score of 83.45% and the results of student activity observations obtained an average score of 87.07% which shows that the use of the MALABARU application has a positive impact on the learning process. Based on these results, the MALABARU application is considered very good and very suitable for use as a learning medium for spatial geometry material in grade V of Elementary School.